اردو شاعری کا مزاحمتی رویہ: قدیم دور: RESISTIVE ATTITUDE OF URDU POETRY: ANCIENT ERRA (Al-Aasar, 2025)
The term resistance literature may have been first coined by Palestinian writer Ghassan Kanafani or Barbara Harlow, but it is certain that the term resistance literature came into existence during the dictatorship era. Thus, on the one hand, literature written for the liberation of Vietnam, Palestine, and Algeria was called resistance literature, while on the other hand, literature written to encourage the marginalized population was also considered resistance literature. Writers have always lit the lamps of truth and justice against the darkness of oppression and oppression. Every true poet and writer stands with the oppressed. The famous French intellectual Sartre criticizes the government of his own country against the French occupation of Algeria and leads a protest movement. Despite the worsening situation, the French ruler of the time refuses to arrest him on the grounds that Sartre is a French intellectual and the intellectuals of the whole of France cannot be handcuffed. In Urdu, the ancient poetic genres “City of Riots” and “Elegy” can be presented as the initial impressions of resistance literature because these genres actually reflect these social It expresses a rejection of the forced exploitation of cultural attitudes and behaviors that enter human life under political and social pressure. When a poet gives a creative color to this forced behavior and culture in his words in the genre of "Elegy" or "City of Riots", we accept it in the category of resistance literature.